Linguistic Validity and Reliability of Urdu Version of Psychosocial Impact of Dental Aesthetic Questionnaire PIDA For Orthodontic Patients in Lahore, Pakistan - Hazik Bin Shahzad; Faiza Awais; Anas Imran Arshad; Dalia Iftikhar; Noor Ul Huda; Wan Muhamad Amir W Ahmad (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: Psychosocial Impact of Dental Aesthetic questionnaire (PIDAQ) is an efficient subjective measure for quality of life. The purpose of this study was to assess the linguistic validity and reliability of the URDU version of the PIDAQ. Methods: PIDAQ questionnaire in English was selected and translated to Urdu language. This process included forward translation and backward translation. The primary draft was then discussed in detail is a committee of different personnel including public health professional, orthodontists, and translators. Pretesting was conducted at Rashid Latif Dental College in Lahore involving ten participants via face-to-face interviews. Inclusion criteria in- cluded all patients coming for orthodontic treatment, that had not yet started their treatment and were able to read and comprehend in Urdu language. Exclusion criteria included those who had any other underlying treatment needs such as caries or periodontal treatment and or any mental or learning disability. The pretest included face to face interviews with 10 subjects to further clarify the understanding and cultural significance of the translated questions. A test-retest reliability study was undertaken over a period of two weeks involving another 24 patients. Cronbach and kappa scores were calculated to assess the sematic, idiomatic, experimental, conceptual as well as content and face validity of the questionnaire. Twenty-three translated questions under four subscales were produced. Results: The Intraclass correlation coefficient values achieved for the translation were between 0.81 to 0.97 for the multiple subscales. The Cronbach was 0.91 for dental self-confidence, 0.81 for social impacts, 0.88 for psy- chological impacts and 0.97 for aesthetic concerns. Conclusion: The PIDAQ-Urdu appeared to be linguistically valid and reliable with excellent test-retest results.